A Systematic Review on the Usability of Web-Based Applications in Advocating Consumers on Food Safety - Wen-Li Seow; Umi Kalsom Md Ariffin; Sook Yee Lim; Nurul Azmawati Mohamed; Kai Wei Lee; Navin Kumar Devaraj; Syafinaz Amin-Nordin (Multidisciplinary Digital Publishing Institute (MD, 2024)
Indexed by WOS/SCOPUS/ERA